In Silico Analysis of Inhibitor Potential of Punicalagin Compound in Pomegranate (Punica granatum) Against NS5 DENV-3 Protein - Kautsar, Radinal; Rachmawati, Yuanita; Rokhim, Saiku; Sucipto, Teguh Hari; Damayanti, Mamik; Ramadhani, Aisyah Hadi (Institute of Topical Disease Universitas Airlangga, 2024)
Indonesia is one of the Dengue Virus (DENV) endemic areas which are dominated by DENV-2 and DENV-3. Until now, no specific drug therapy has been found to cure Dengue Virus Infection (DVI). Punicalagin is one of the active compounds that have the potential to be used as an antiviral. Unfortunately, not many studies have used punicalagin as a DENV antivirus. This study aims to determine the inhibitory potential of punicalagin compounds against NS5 DENV-3 protein through molecular docking. Molecular docking was performed using AutoDock Tools, ChemDraw, and Discovery Studio Visualizer. The target protein used is NS5 DENV-3 protein with PDB ID code: 4V0Q. The ribavirin compound was used as a positive control. The results obtained show that the punicalagin compound has the ability to attach to target receptors in the C-Terminal domain complex. This docking produces a bond free energy (Î”G) of -6.39 kcal/mol. This result is better than the Î”G of the control compound. Punicalagin's Inhibition Constant (Ki) value also showed better results than ribavirin. So it can be seen that the compound punicalagin effectively inhibits DENV replication and has the potential as a DENV drug candidate.